Enrichment of commercial feed for striped snakehead fry (Channa striata) with golden snail (Pomacea sp.) flour. (November 2019) - Ndobe, S; Mangitung, S F; Bardi, R; Madinawati,; Tobigo, D T; Moore, A M
Abstract: The striped snakehead Channa striata is a highly nutritious and economically valuable food fish. Wild populations are declining due to habitat degradation and conversion as well as overexploitation. To promote sustainable use of this resource, a striped snakehead domestication program was initiated in 2013. Earlier research found that golden snail ( Pomacea sp.) was suitable as a natural feed for the grow-out of striped snakehead juveniles. This study focused on the formulation of feed for fry, applying a fully randomised experimental method with 5 replicates. Each experimental unit (aquarium with aeration) contained four striped snakehead fry (total length 3.42 ± 0.21 mm). The feed treatments used commercial HI-PRO-VITE 782 feed, with golden snail flour added in 4 doses: A (0%), B (20%), C (25%), D (30%). Total length and weight were measured weekly; water quality and survival were monitored. Overall, the length-weight relation was allometric negative. In terms of both length and weight, growth was highest under treatment C and lowest under treatment A. Growth was significantly different between treatments: A and C for length and weight (analysis of variance with Tukey post-hoc test, α=0.05). Growth patterns and condition factor varied between treatments, with treatment C yielding better balanced growth compared to B (slower increase in length) and D (slower weight gain). Survival rate did not differ significantly between treatments. We conclude that enrichment of commercial feed (HI-PRO-VITE 782) with golden snail flour can improve striped snakehead fry growth, with 25% the most effective dose.